Comportement, conduite et bien-être animal - Manteca i Vilanova, Xavier (éditions Quae, 2014)
This work outlines the general principles and recommendations on the raising of domestic animals applied to the Southern countries, especially tropical regions. These recommendations are important in a context of intensification of farms (dairy, poultry, etc.) and changes in conventional farming. They address the "